IMPACT OF POST-HARVEST PEST INFESTATION ON MAIZE (ZEA MAYS) PRODUCTION IN ISOKO SOUTH LOCAL GOVERNMENT AREA, DELTA STATE - Igene, C. A.; Belonwu, N. E.; Iloba, L.C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the impact of post-harvest pests on maize production in Isoko South Local Government Area (LGA), of Delta State, Nigeria. The research examines the socio-economic characteristics of maize farmers, pest control practices, the effects of pests on maize yield, and the challenges faced by farmers in managing pest infestations. Data were collected from 50 farmers across five local communities using a closed-ended questionnaire and a multi-stage random sampling technique was used to select the respondents. Descriptive statistics and regression methods were employed for data analysis. The findings revealed that most farmers (63.3%) were male, middle-aged, and had at least secondary education. A majority (74%) implemented pest control measures, with cultural control being the most common method. However, 67.3% of farmers reported moderate pest damage, and 14.3% experienced severe damage to their maize crops. Yield losses varied, with many farmers reporting losses of up to 10%, and yields ranging from less than 2 tons to over 6 tons per hectare. Key challenges identified include a lack of knowledge on pest control methods (81.6%), limited access to pest control resources (75.5%), and the high cost of pest management (85.7%). Regression analysis showed significant correlations between farmers' characteristics and post-harvest pest impact. Gender (B = 1.409, p = 0.000), age (B = 0.357, p = 0.017), education (B = 0.662, p = 0.000), marital status (B = -0.208, p = 0.002), and farming experience (B = 0.685, p = 0.000) all influence pest management. The study recommends improving pest management strategies through education on Integrated Pest Management (IPM), better access to pest control resources, government subsidies for pest control, and investment in pest-resistant maize varieties. Additionally, enhancing storage facilities and promoting sustainable pest control practices are vital for increasing maize productivity and reducing post-harvest losses.